A Numerical Study on the Influence of Bolt Corrosion on the Long-Term Behavior of Steel–Concrete Composite Beams - Yalei Niu; Chen Qu; Qingxing Feng (Advances in Civil Engineering)
This study establishes a numerical model for beam-type steel–concrete composite specimens considering the corrosion of anchor bolts, with which studies the long-term deformation performance of the components under sustained load. The experimental results were compared with the calculated values obtained by combining the effective modulus method according to the CEB-FIP 1990 code and the ACI 209R code. Then a comparison with the calculation method of shrinkage and creep in standards (Standard Creep Method (SCM)) is made, and it shows that by supplementing the degradation of interface stiffness due to corrosion (using the defined modulus method (DMM)), the simulation results match better with the experimental results, confirming that this approach is suitable for analyzing the long-term load conditions of anchor bolt corrosion. Furthermore, based on the defined modulus method, the long-term behavior of composite beams under different loads and varying corrosion rates is studied.